The Effect of Audit Tenure, Firm Size, Level of Audit Fees, Independence, and Competence on Audit Quality at the North Sumatra Provincial BPKP - Bunga Ristama Sagala; Rospinuryani Sinaga; Margaretha Br Sitinjak (Asian Journal of Management Analytics, 2026)
This study aims to examine the influence of audit tenure, company size, level of audit fees, independence, and auditor competence on audit quality at the North Sumatra Financial and Development Supervisory Agency (BPKP), both partially and simultaneously, as well as provide recommendations in the context of improving financial supervision standards. This study uses a quantitative approach with a survey method, where data is obtained through the distribution of questionnaires to North Sumatra BPKP auditors as research respondents. The analysis techniques used include statistical analysis, validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), determination coefficient (R²) tests, F tests, and t tests. The results of the study provide strategic implications for BPKP North Sumatra in improving the quality of financial supervision through strengthening human resources.